1983
DOI: 10.1016/s0735-1097(83)80151-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of lipomatous hypertrophy of the atrial septum by two-dimensional echocardiography

Abstract: Originally described in 1964, lipomatous hypertrophy of the atrial septum currently remains a diagnosis established primarily at autopsy. Clinical interest in this disorder has centered on the reported association with supraventricular arrhythmias and sudden death. Because two-dimensional echocardiography allows detailed assessment of atrial septal configuration, we reviewed two-dimensional echocardiographic reports obtained over a 1 year period and identified 17 patients who had features consistent with lipom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 6 publications
2
21
0
1
Order By: Relevance
“…2 This clinical entity is a disorder characterized by excessive accumulation of adipose tissue within the interatrial septum, resulting in a globular thickening of the interatrial septum. 3,4 Infiltration of adipose cells between atrial myocytes with a small amount of interstitial fibrosis, or a mixture of fat and cardiac myocytes were described as the microscopic findings as shown in the present case. 5 Burke and Virmani 5 reported that lipomatous hypertrophy is a rare lesion, and approximately 200 cases have been reported.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…2 This clinical entity is a disorder characterized by excessive accumulation of adipose tissue within the interatrial septum, resulting in a globular thickening of the interatrial septum. 3,4 Infiltration of adipose cells between atrial myocytes with a small amount of interstitial fibrosis, or a mixture of fat and cardiac myocytes were described as the microscopic findings as shown in the present case. 5 Burke and Virmani 5 reported that lipomatous hypertrophy is a rare lesion, and approximately 200 cases have been reported.…”
Section: Discussionsupporting
confidence: 66%
“…Several authors 4,10 have emphasized the usefulness of 2-dimensional echocardiography, both transthoracic and transesophageal for detecting lipomatous hypertrophy of the interatrial septum. However, the 2-dimensional echocardiographic appearance of lipomatous hypertrophy of the interatrial septum may not be specific enough to establish this diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On cross-sectional echocardiography, the septum appears like a "dumbbell." 35 Even in hearts without so-called "septal hypertrophy," transgression through the rim can hinder needle penetration, and, being a thicker structure, can restrict maneuverability after crossing and also increase the risk of exiting the heart, dissecting into the fatty tissue plane, and causing hemopericardium. At particular risk is the anterior rim of the fossa, which is in close anatomic relationship with the aortic mound.…”
Section: Septal Componentmentioning
confidence: 99%
“…it consists histopathologically of varying proportions of mature adipose tissue, fibrosis, inflammation, and fetal fat cells, the presence of which is a hallmark of lipomatous hypertrophy of the atrial septum (2-4). This condition, albeit mostly benign, has been associated with atrial arrhythmias, congestive right-sided heart failure, atherosclerotic coronary artery disease, and sudden death (2,5). In most cases, these unencapsulated lipomas extend from the coronary sinus to just above the level of the aortic root with relative sparing of the fossa ovalis, which results in a typical dumbell configuration on computed tomography and echocardiography (1.6).…”
mentioning
confidence: 99%